Removal of Ear Wax by Suction versus Syringing - Zmnako, Sherko S. F. (Sulaimani Journal for Pure and Applied Sciences, 2001)
A prospective comparative study carried out on fifty patients complaining from bilateral impacted ear wax, to compare the efficiency of suction with that of syringing during removal of wax. In each patient right ear was cleaned by suction and left ear by syringing. We concluded from the study that suction in comparison with syringing is more effective in cleaning the ear (80%). Less causing injection of the drumhead (4%). more preferable by the patient (92%).
Keywords: Removal of Wax